2017
DOI: 10.1111/arcm.12299
|View full text |Cite
|
Sign up to set email alerts
|

A Better Shade of Black: Effects of Manufacturing Parameters on the Development of Ancient Black Bronzes*

Abstract: Copper alloys with controlled contents of Sn, Ag and Au were treated with methods and solutions that mimic those used in ancient and traditional procedures for the production of black bronze. Examination of the resulting patinas with colorimetry, SEM–EDS, TEM, Raman spectroscopy and XRD revealed no systematic differences according to the fabrication method, whereas patina homogeneity and colour in those alloys that did not contain precious metal were affected by superficial work. Patina microstructure determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The earlier experiments [17] also showed that the most successful patinas, comprising compact and homogeneous layers of fine grains covering the entirety of the sample surface, were obtained using a copper acetate treatment solution, the main documented ingredient to have been used in Japanese patination. Therefore, in the present study, the patination was performed on a hotplate with a copper acetate solution (0.4 g in 100 ml of deionised water).…”
Section: 1: Experimental Patinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The earlier experiments [17] also showed that the most successful patinas, comprising compact and homogeneous layers of fine grains covering the entirety of the sample surface, were obtained using a copper acetate treatment solution, the main documented ingredient to have been used in Japanese patination. Therefore, in the present study, the patination was performed on a hotplate with a copper acetate solution (0.4 g in 100 ml of deionised water).…”
Section: 1: Experimental Patinationmentioning
confidence: 99%
“…The experimental method was based on the results of the pilot study described in Benzonelli et al [17]. We produced replica tokens of eight alloys, four of which were included in the original experiments: Cu 100 , Cu 95 Sn 5 , Cu 97 Au 3 , and Cu 89 Sn 5 Au 3 Ag 3 plus four new compositions: Cu 97 Ag 3 , Cu 92 Sn 5 Au 3 , Cu 92 Sn 5 Ag 3 , and Cu 94 Au 3 Ag 3 , where subscripts indicate the composition in wt.%.…”
Section: 1: Experimental Patinationmentioning
confidence: 99%
See 1 more Smart Citation
“…• Lehm (Sugimori 2004;Benzonelli et al 2017Benzonelli et al , 1042 414 When thinking of "natural" grinding and polishing agents, mainly sandstone, quartz sand and maybe natural emery spring to mind. Old handbooks for craftsmen and workshop equipment -plus a very few sources of information from antique authors -deal with many other substances which could either be used for sanding or for polishing.…”
Section: Material Aufbereitung Und Beobachtungen Im Experimentsmentioning
confidence: 99%
“…1060 Ogden 1993, 40-2;Demakopoulou et al 1995. See also Aruz et al 2008Cockrell 2009, 85-9;Benzonelli et al 2017, 11-3. 1061Demakopoulou et al 1995Giumlia-Mair 2012, 107, 111-14.…”
Section: Polychromymentioning
confidence: 98%